The Impact of Work Motivation and Employee Development on Surabaya City's Fire Fighting and Rescue Department Employee Performance - Rohmah Kurniawati; Waloyo waloyo (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The City of Surabaya's rescue and fire departments plays a crucial role in government administration in the areas of community protection for firefighters and public peace and order. The goal of this study was to evaluate how employee development and job motivation impacted the performance of firefighters and rescue workers in Surabaya. Design/methodology/approach: Descriptive quantitative and case study methodologies are the research methodology applied. Techniques for collecting data are questionnaire. Multiple linear regression analysis is used in the analysis, and SPSS 26 is used to process the data. Findings: According to the study's findings, the variable Work Motivation (X2) is 4.079 > t table value of 1.684, while the variable Employee Development (X1) is partially positive and significant at 5.746 > t table value of 1.684. The concurrently determined F value of 103.004 > F table of 2.32 is positively and significantly impacted by the employee development factors (X1) and work motivation (X2), respectively. Practical Implication: The government will use the practical implications as a starting point for evaluating the Fire and Rescue Service employee ’s performance policies. Theoretical implications can be used as a guide for future studies on employee performance in the field of theory. Paper type: Research paper